2021
DOI: 10.2147/ijgm.s318876
|View full text |Cite
|
Sign up to set email alerts
|

How Much Benefit Can Patients Acquire from Enhanced Recovery After Surgery Protocols with Percutaneous Endoscopic Lumbar Interbody Fusion?

Abstract: Purpose We aimed to explore the role of enhanced recovery after surgery (ERAS) in patients who underwent percutaneous endoscopic lumbar interbody fusion (PELIF). Patients and Methods We performed a retrospective, observational, cohort study on 91 patients who underwent PELIF for degenerative disc disease. The primary outcomes were postoperative opioid consumption, hospital length of stay (LOS), and hospital cost. Results Forty-six patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Most studies evaluated a fast-track protocol (81%) versus a conventional (non-fast track) protocol (19%), reporting a significantly reduced LOS (in 81% of studies), without increasing complication or readmissions rate in patients treated with fast-track, regardless of follow-up (from 1 month to 2 years), pathology and surgical approach used. Four studies instead reported no significant differences in LOS between the fast-track and non-fast-track groups [ 16 , 33 , 51 , 53 ]. Complication rates with fast-track protocols ranged from 1.5 to 26%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies evaluated a fast-track protocol (81%) versus a conventional (non-fast track) protocol (19%), reporting a significantly reduced LOS (in 81% of studies), without increasing complication or readmissions rate in patients treated with fast-track, regardless of follow-up (from 1 month to 2 years), pathology and surgical approach used. Four studies instead reported no significant differences in LOS between the fast-track and non-fast-track groups [ 16 , 33 , 51 , 53 ]. Complication rates with fast-track protocols ranged from 1.5 to 26%.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, for maintenance of anesthesia, inhalational agents such as sevoflurane, isoflurane and desflurane, or intravenous opioid agents such as sufentanil or remifentanil infusions were used. In 21% of studies, a local anesthesia with anesthetic agents as bupivacaine, lidocaine or ropivacaine was employed [ 18 , 27 , 28 , 33 , 35 , 45 , 48 , 63 , 65 , 66 , 70 , 71 ]. Regarding analgesia management, pain scores were tracked in 30 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, endoscopic techniques further reduce the length of stay associated with MIS surgeries [ 7 , 39 , 40 ]. Though a recent retrospective study failed to corroborate this finding, it did suggest that percutaneous endoscopic LIF was associated with improvements in analgesia and decreased opioid usage, another potential benefit [ 41 ]. In a recent review, Wang et al found that endoscopic TLIF saved the healthcare system an average of $3444 when compared to standard MIS TLIF [ 40 ].…”
Section: Endoscopic Techniques In the Broader Context Of Lumbar Inter...mentioning
confidence: 99%